2019
DOI: 10.1097/cad.0000000000000686
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic effects of novel thiazole derivative on human glioma cells

Abstract: The aim of the present study was to investigate the antiproliferative and proapoptotic actions of N-(5-benzyl-1,3-thiazol-2-yl)-3,5-dimethyl-1-benzofuran-2-carboxamide derivative (compound 5) in glioma cells in comparison with the actions of temozolomide (TMZ) and doxorubicin (Dox), used as positive controls. The antiproliferative activity of the compound 5, TMZ, and Dox on human glioblastoma U251 and human glioblastoma multiform T98G cells was measured using the MTT test. Western blot analysis, fluorescent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…In our previous studies, we found that the novel thiazole derivatives BF1 and PP2 activate caspasedependent and mitochondria-associated mechanism of apoptosis [6,7]. In order to reveal potential morphological changes in mitochondria in NK/Ly lymphoma cells under treatment with BF1 and PP2, we have carried out the electron microscopy study of these cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, we found that the novel thiazole derivatives BF1 and PP2 activate caspasedependent and mitochondria-associated mechanism of apoptosis [6,7]. In order to reveal potential morphological changes in mitochondria in NK/Ly lymphoma cells under treatment with BF1 and PP2, we have carried out the electron microscopy study of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds also had low toxicity towards human kidney cells (HEK 293) and human keratinocytes (HaCaT line) [5,8]. Previously we have identified that BF1 increased the level of Bax and Bim pro-apoptotic proteins in glioma cells [6], and PP2 increased the level of pro-apoptotic Bim protein and the mitochondriaspecific EndoG nuclease, and decreased the level of the anti-apoptotic Bcl-2 protein in the leukemia cells in vitro [7].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…For calculation of the olive tail mo-ment (OTL), Casplab-1.2.3b2 software (CASPLab, Wroclaw, Poland) was used. OTL was studied as a product of the detectable DNA in the comet tail, and distance between centers of the head mass and tail region, and calculated as OTL = (Tail mean -Head mean)×% of tail DNA [9,10].…”
Section: Methodsmentioning
confidence: 99%
“…Gel retardation assay of plasmid DNA. Plasmid DNA (1 μg/μl) pEGFPc-1 (Clontech, Mountain View, California, USA) was mixed with 2 μl of compounds 1, 2 (0.09, 1.0, 10.0 μM), and Dox (0.09 μM) in 18 µl of 0.9% sodium chloride (Arterium, Lviv, Ukraine) at room temperature for 1 h. The prepared mixture was analyzed by electrophoresis in 1% agarose gel (Lachema, Brno, Czech Republic) with 1× Tris acetate (TAE) buffer containing 1 μg/ml of EtBr (Sigma-Aldrich, St. Louis, Missouri, USA) for 1 h at a constant voltage of 70 V. A trans-illuminator (MacroVue UV-20, Hoeffer Pharmacia Biotech Inc., San Francisco, California, USA) was used for visualization of plasmid DNA [10].…”
Section: Methodsmentioning
confidence: 99%